2020
DOI: 10.1186/s13643-020-01328-3
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of network meta-analyses assessing the efficacy and safety of complementary and alternative medicine interventions

Abstract: Background Network meta-analysis (NMA) has rapidly grown in use during the past decade for the comparison of healthcare interventions. While its general use in the comparison of conventional medicines has been studied previously, to our awareness, its use to assess complementary and alternative medicines (CAM) has not been studied. A scoping review of the literature was performed to identify systematic reviews incorporating NMAs involving one or more CAM interventions. Methods An information specialist execut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 121 publications
1
14
0
Order By: Relevance
“…To the best of our knowledge, this is the largest review assessing the PRISMA extension guideline for NMA in more than 1,000 systematic reviews and NMAs. Our ndings are aligned with previous ndings by Hutton et al, (11) who evaluated 89 NMAs of non-pharmacological therapies, Tonin et al (10) who assessed 477 NMAs of pharmacological treatments, and Lee and Shin ( 9) who assessed 21 NMAs in dental care. In agreement with assessments in systematic reviews and meta-analyses, reporting in the 27 core PRISMA items was suboptimal.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To the best of our knowledge, this is the largest review assessing the PRISMA extension guideline for NMA in more than 1,000 systematic reviews and NMAs. Our ndings are aligned with previous ndings by Hutton et al, (11) who evaluated 89 NMAs of non-pharmacological therapies, Tonin et al (10) who assessed 477 NMAs of pharmacological treatments, and Lee and Shin ( 9) who assessed 21 NMAs in dental care. In agreement with assessments in systematic reviews and meta-analyses, reporting in the 27 core PRISMA items was suboptimal.…”
Section: Discussionsupporting
confidence: 90%
“…A scoping review of 89 NMAs with complementary and alternative medicines published up until 2018 showed that the PRISMA-NMA guideline was overall adequately adopted through key reporting items such as the existence of a protocol, exploring network geometry, and risk of bias assessment were often missing (up to 65%). (11) As previous empirical research has suggested that reporting of NMAs is improving over time, it is unclear whether the PRISMA-NMA statement has accelerated this improvement. Our objective was to empirically assess whether the PRISMA-NMA statement had an important impact on the completeness of reporting by comparing NMA articles of randomized controlled trials (RCTs) between two time periods (2013-2015 and 2016-2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are aligned with previous findings by Hutton et al . [ 11 ], who evaluated 89 NMAs of non-pharmacological therapies; Tonin et al [ 10 ] who assessed 477 NMAs of pharmacological treatments; and Lee and Shin [ 9 ] who assessed 21 NMAs in dental care. In agreement with assessments in systematic reviews and meta-analyses, reporting in the 27 core PRISMA items was suboptimal [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tonin et al [ 10 ] assessed the extend of compliance with PRISMA (for NMAs published before 2015) and PRISMA-NMA (for NMAs published between 2015 and end of 2016) in 477 NMAs of pharmacological treatments and showed minor improvement in reporting according to the PRISMA score. A scoping review of 89 NMAs with complementary and alternative medicines published up until 2018 showed that the PRISMA-NMA guideline was overall adequately adopted through key reporting items such as the existence of a protocol, exploring network geometry, and risk of bias assessment were often missing (up to 65%) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in other fields of non-pharmacological treatment of RD, such as physiotherapy, psychotherapy, balneology, and rehabilitation, limited access to research funding for the effectiveness of CAM has led to a slow increase in scientific evidence. However, recent publications have confirmed the interest in CAM as a research field, particularly in China, with most research dealing with herbal or dietary supplements [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%